PENGEMBANGAN KEMITRAAN KA WASAN MATEMATIKA(MATH MASTER ZONE) DI KECAMATAN SA WAHAN KABUP ATEN NGANJUK - Muhtadi, Muhtadi; Sutama, Sutama; Anif, Sofyan; Prayitno, Harun Joko (WARTA, 2015)
PEMITRA service activities in the kecamatan Sawahan kabupaten Nganjuk, had conducted educational activities, training, and mentoring for elementary school teachers, principals, supervisors and the person in charge of Math Masters Zone program to improve the basic concepts of mathematics and its teaching method. In this Pemitra conducted training activities learning methods of Math Masters, so that teachers had  an understanding  and basic  mathematical concepts  were true,  and instructed it so easy and fun to their students. In the implementation of this Pemitra service activities, had given results and achievements were very enjoyable because math test scores elementary school students in the kecamatan Sawahan on the 2013/2014  school  year  had  average  to  8.5  and  the  highest  value  reached  10.0.  Math Olympiad  activities  also quite  lively, as  students becomed  more enthusiastic  andexcited. Based on indicators of progress and this proves that the method Math Master who had been introduced by the Executive Team Pemitra, had helped to solve problems Numeric  Phobia  for  elementary  school  students  in  the  kecamatan  Sawahan. Mathematics was considered subjects which so easy and very fun by the students.Constraints and problems still be faced today is the support and consistency of Nganjuk government has not been consistent in developing subdistrict Sawahan as Math Master Zone.